Risk factors for diagnosed noma in northwest Nigeria: A case-control study, 2017 - Farley, Elise; Lenglet, Annick; Ariti, Cono; Jiya, Nma M.; Adetunji, Adeniyi Semiyu; van der Kam, Saskia; Bil, Karla (PLOS Neglected Tropical Diseases, 2018)
Author summary Noma or cancrum oris is an orofacial gangrene that rapidly disintegrates the hard and soft tissue of the face. Little is known about noma as most cases live in underserved, difficult to reach locations. There is a dearth of literature on the risk factors for the development of noma. Médecins Sans Frontières (MSF) in collaboration with the Nigerian Ministry of Health runs projects at the Noma Children’s Hospital in Sokoto. A case control study was conducted in northwest Nigeria to explore exposures associated with diagnosed noma using unadjusted and adjusted conditional logistic regression models. Potential risk and protective factors for diagnosed noma were identified and these findings need further exploration. The study identified that feeding pap to the child every day was a potential risk factor for diagnosed noma (possibly a proxy for poor variety in the diet). The following potential protective factors for diagnosed noma were identified: the mother being the primary caretaker, the caretaker being married, and colostrum being given to the baby. Noma is a neglected disease, and current risk factors suggest that intervention efforts could be more effective by focussing on access to health care, the benefits of breastfeeding and a varied diet. However, more research is needed in order to better understand the pathogenesis of this disease in order to improve prevention, early detection and treatment.